OWL-S ComposerW: Composição de Serviços Web Semânticos SOAP e RESTful - Queiroz , Adriano Novais; Claro, Daniela Barreiro (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
Our proposed web tool called OWL-S ComposerW aims to develop heterogeneous semantic compositions in a visual manner. Its main objective is to interoperate SOAP and RESTful web services to embed into devices. This tool was evaluated in two fold: a case study and a questionnaire ﬁlled by developers. Our results stated that OWL-S ComposerW is considered useful and achieves its main proposal to visual compose heterogeneous services.